Educating the neoliberal whole child : a genealogical approach - Jones, Bronwen MA (Abingdon, Oxon ; New York, NY : Routledge, 2022)
This book questions what educating the whole child' means in the context of our current neoliberal education system. In analysing the impact of how education policy is enacted and understood, it examines how this neoliberalisation' has shaped the personal and ethical relations of education. The book is unique in raising questions about the way in which a common and universally held truth about the importance and value of educating the whole child is conceptualised and articulated in education policy. Employing Foucault's concepts of bio power, governmentality, the dispositif and subjectivities, this book explores the importance of psy-scientific knowledge, systems of education governance and classroom practices in constructing a neoliberal whole child. It examines how government policy structures the relationship between the child, school and government and claims that current policy and practice operate as forms of bio power that extends neoliberal governance to the emotional and moral life of the child. Educating the Neoliberal Whole Child will be of great interest to researchers, academics and students in the fields of education policy, sociology of education and critical pedagogy. It is also a valuable addition to studies of Foucault and education.
Keywords: Education and state; Educational sociology; Neoliberalism; EDUCATION / Educational Policy & Reform / General